Vortex-induced vibration of a full-diamond textured cylinder at subcritical Reynolds numbers. (May 2022) - Nikoo, Hamid Matin; Bi, Kaiming; Hao, Hong
Abstract: Textured pipe has been proposed to improve the propagation buckling capacity of subsea pipelines recently. Due to its special geometry, textured pipe may have the potential to mitigate the vortex induced vibration (VIV) by altering the wake vortex street formation. In the present study, the effectiveness of using a full-diamond textured pipe for VIV suppression is numerically investigated in a coupled fluid-structure interaction (FSI) framework. Three-dimensional (3D) Computational Fluid Dynamics (CFD) analyses are performed by using the Reynolds-Averaged Navier-Stokes (RANS) turbulence model equipped with shear stress transport ( S S T ) K − ω model at the subcritical Reynolds numbers ( R e ) with R e ∈ [ 2000, 12000 ] . The results are compared in detail with an equivalent conventional smooth cylinder subjected to the same flow conditions. Numerical results show that the textured cylinder can significantly mitigate the undesired VIV and the associated hydrodynamic forces. It eliminates the upper excitation regime in the conventional smooth cylinder and the width of the synchronization regime is also remarkably reduced. Highlights: 3D CFD analyses are carried out to investigate the effectiveness of using textured pipe for VIV suppression. The responses are compared with an equivalent smooth cylinder. It is found that textured cylinder can significantly mitigate the VIV responses.